SBAS-InSAR-Based Analysis of Surface Deformation in the Eastern Tianshan Mountains, China - Du, Qingsong; Li, Guoyu; Chen, Dun; Zhou, Yu; Qi, Shunshun; Wu, Gang; Chai, Mingtang; Tang, Liyun; Jia, Hailiang; Peng, Wanlin (Frontiers in Earth Science, 2021)
Due to the unique geographical characteristics of cold alpine and high-altitude regions, glaciers, permafrost, ground ice, rock glaciers, and other periglacial geomorphology have developed with fragile habitats, and these areas are often the birthplace of many river basins and natural hazards. With global warming and the extensive cryogenesis and physical weathering, then deduced that the surface deformation is of great concern. To obtain ground subsidence or uplift over a large area to understand local surface changes, the small baseline subset interferometric synthetic aperture radar (SBAS-InSAR) technique was applied to process 89-scene of Sentinel-1A images ranging from 25th December 2017 to 2nd January 2021 to obtain surface deformation for these three years for the eastern Tianshan Mountains, China. The surface deformation characteristics of the area were analyzed to provide a basic dataset for environmental protection policies and mitigation or reduction of natural hazards in this region, and to verify the applicability of SBAS-InSAR technology in alpine and high-altitude areas. The results show that the SBAS-InSAR technique processing with sentinel-1a dataset cannot be effectively used to acquire ground deformation in areas covered by trees, scrub/shrub, glaciers, snow, and ground ice, where the decohered phenomenon is serious. In other regions, SBAS-InSAR can effectively measure surface subsidence or uplift. Surface deformation is significant throughout the study area, with rates ranging from -70.71 mm/a to 50.83 mm/a and with an average rate of 1.10 mm/a. There are obvious regions of uplift in the northwest, northeast, and central sections of the study area, with uplift greater than 155.73 mm in three years, and three obvious regions of subsidence in the northeast and west sections of the study area, with subsidence of at least -125.20 mm in three years. The remaining areas of deformation are scattered, with smaller amounts of settlement and uplift and with an isolated and sporadic distribution. Areas with elevations of 3,150 to 4,275 m.a.s.l., slopes of 15° to 50°, and southeast, south, and southwest aspects are geologic disaster-prone regions and should receive more attention and more field monitoring. The results of this study have important implications for local environmental protection and hazard prevention.